A Comparative Study of Male and Female Characters in Selected Dramas of Khalil-ur-Rehman Qamar - Bushra Sharif; Dr. Shahida Rasool (Zaban-o-Adab, 2025)
Drama is a relatively modern of literature in fiction .It is the only medium of literature that directly affects society and the social system. Because other medium of literature are related to speech and hearing, while drama is related to movement and vision, and humans naturally have the ability to accept immediate effects by seeing things happening. Since drama is the name of the presentation of social facts, in real life, the social system cannot progress in the absence of either man or woman. Since literature is the second name of life, any medium of literature without men and women is incomplete. Most writers interpreted the attitudes that were prevalent in society regarding men and women, while the writer also has the responsibility of reforming the society. If the society is suffering from directionlessness and misguidance, then a creator should be brave and dutiful enough to introduce positive moral and constructive thinking at the social level, regardless of prevailing tradition. The play writer is authorized to change the thinking of the viewer with the drama he creates.